Is There Any Chance for Crop and Livestock Integration in Indonesia? - Bambang R Prawiradiputra (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
The integration of livestock and crops, especially food crops, or recently known as crop-livestock systems is very familiar in Indonesia as well as in South-East Asia. The system has been practiced for decades and still carrying out until now. In Indonesian traditional farming system, livestock plays an important role in the system. In Indonesia, there are five types of farming system namely extensive farming, non-intensive farming, intensive farming, very intensive farming and conservation farming system. However, there are some constraints in each system. This paper describes some constraints in Indonesian farming systems especially in crop-animal systems, such as land, manpower, money, technology, informations and farmer organization.   Key words: Integration, farming systems, crops, livestock, constraints